B- Acute Lymphoblastic Leukemia L2 In Second Trimester of Pregnancy - Iraisa rosaria; Dwi Retnoningrum (Faculty of Medicine, Diponegoro University, 2021)
Background: Acute lymphoblastic leukemia (ALL) in adults tends to have a poor prognosis and even more challenging to treat during pregnancy due to the mother and the fetus’s safety issue. Despite commonly found in 2nd and 3rd trimester, ALL found during 2nd trimester needs more comprehensive management on maintaining the pregnancy while chemotherapy cannot be delayed.Case Presentation: A 36-year-old woman at 27 weeks of gestation visited the hospital with multiple cervical lymphadenopathy and major weight loss for the last six months. Bicytopenia with leukocytosis is found, along with an increase in LDH, Ferritin, and low albumin level. Bone marrow biopsy had confirmed the diagnosis of ALL-L2. Positive immunophenotyping results on HLA-DR, CD10, CD19, CD20, which support the lymphoid Line-B subtype. The patient was treated with Vincristine 2 mg/IV weekly and 100 mg of oral prednisone for six weeks and maintain the pregnancy. Successful delivery was carried out at 32 weeks of gestational age by lower segment cesarean section due to premature rupture of the membrane. A baby girl was born weighed 1700 gram, APGAR Score 8/9/9, and has no disability on clinical or hematological features at the moment.Conclusion: ALL in pregnancy is very rare and extremely aggressive disease unless promptly treated. In this case report, it was a first pregnancy in advanced maternal age mother with high social value baby and can be treated succesfully using single regimen of chemoteraphy during pregnancy even though at the first time administered to hospital the mother come with critical clinical presentation. Leukemia in pregnancy is challenging and still need further study to increase the safety and better treatment outcome.Keywords: ALL in pregnancy, ALL-L2, Line-B Lymphoid, Immunophenotyping ALL